Behavioural insights as the example of innovative approach to public policymaking - Miłaszewicz, Danuta (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: Among the theorists and practitioners of public policy is growing awareness of the need to change the assumptions of designing and implementing public policy. The findings of social sciences, especially behavioural economics and experiments used within it, provide knowledge on how within public policy to influence the way people think and make decisions. Using behavioural insights in public policy is innovative opportunity to significantly increase the effectiveness of many public activities. Aim: The purpose of this article is to analyse behavioural insights as an innovative approach to public policy making and the current strategies for the policy and design of public regulations based on them. Results: Based on the literature on the subject and the analysis of the experience of nudge units, the principles of introducing behavioural insights as an innovative approach in public policy were indicated. They are currently being refined and recommended as ready-to-apply strategies for behavioural changes.